Strength of Strained Two‐Phase Mixtures: Application to Rapid Creep and Stress Amplification in Subduction Zone Mélange. Issue 1 (15th January 2019) - Beall, Adam; Fagereng, Åke; Ellis, Susan
Abstract: Aseismic creep may occur by distributed deformation in mélange shear zones comprising weak matrix and stronger clast materials. Slow slip events or steady tectonic displacement can be distributed over <100‐m thick shear zones if weak matrix controls bulk shear zone deformation. We use 2‐D numerical models to quantify the rheology of moderately strained (shear strain <1.75) mélange for various volumetric proportions of competent clasts. Mélange deformation with <50% clasts is matrix dominated and can accommodate steady creep. At higher clast proportions mélange viscosity increases more than tenfold after small strains, because strong clasts interact and form force chains. Clast shear stress is amplified above the imposed shear stress, by a factor of <14 where force chains develop. Slow slip events may occur due to a temporary absence of force chains, while localized regions of high shear stress generate coincident fracturing and potentially tremor events. Plain Language Summary: Some subduction shear zones creep without generating large earthquakes. It is unclear which deformation process at depth allows this creep to occur. We compute numerical models to explore whether creep is promoted by having a particular proportion of weak materials within subduction fault zones, which typically consist of mixtures ( mélanges ) of weak and strong components. We demonstrate that in a mélange that consists of <50% weak minerals, forces are concentrated into force chains of strong materials when the mélange is slightly deformed, resulting in an overall strength which is much greater than previously predicted. Subduction zone creep events therefore occur in mélanges either with a high proportion of weak minerals, or in the temporary absence of such force concentrations. Swarms of very small earthquakes are often associated with creep events, which likely require failure of the stronger mélange materials. We show that large forces are generated in the strong materials, plausibly leading to this failure, even when the overall mélange is very weak. Key Points: Two‐dimensional mélange shear zones require ≥50% weak matrix to accommodate steady creep at low stress; otherwise, force chains lead to jamming Transient creep (slow slip) events may occur in mélange with ≤50% weak matrix during temporary absence of force chains Stress amplification, and potentially tremor, occurs even in steadily creeping mélange